2019
DOI: 10.1111/ppc.12461
|View full text |Cite
|
Sign up to set email alerts
|

Educating children through their parents to prevent child sexual abuse in Turkey

Abstract: Purpose: The aims of this study were to train parents to recognize and prevent child sexual abuse (CSA); evaluate the problems encountered by parents; and evaluate the overall effectiveness of the CSA training program. Design and Methods:The study used a pretest/posttest design. The study was conducted with a sample of 58 children (aged 3-6 years) and 64 parents. Findings: Children who received CSA prevention education from their parents demonstrated improved knowledge about private parts and about what they s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 30 publications
0
24
0
4
Order By: Relevance
“…Czerwinski et al (2018) found that the IGEL prevention program used to prevent child sexual abuse led to an increase in knowledge and action plans related to CSA in children in the intervention group. According to Wulandari et al (2022) Parents need to be knowledgeable to give prevention education to their children (Apaydın Cırık et al, 2020;Apaydın Cırık et al, 2022;Tunç et al, 2018;Zhang et al, 2020). Based on the child sexual abuse knowledge and attitude scores of the fathers in this study, their knowledge/attitude about child sexual abuse is below the moderate level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Czerwinski et al (2018) found that the IGEL prevention program used to prevent child sexual abuse led to an increase in knowledge and action plans related to CSA in children in the intervention group. According to Wulandari et al (2022) Parents need to be knowledgeable to give prevention education to their children (Apaydın Cırık et al, 2020;Apaydın Cırık et al, 2022;Tunç et al, 2018;Zhang et al, 2020). Based on the child sexual abuse knowledge and attitude scores of the fathers in this study, their knowledge/attitude about child sexual abuse is below the moderate level.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Turkey showed that the implementation of a simplified preventive psychosocial intervention for mothers and their children increased the children's knowledge about protection from sexual abuse (Orak & Okanli, 2021). In another study that provided CSA prevention training to parents so that they could educate their children, the children's knowledge levels improved in recognizing their private body parts (Apaydın Cırık et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, Kenny et al (2020) encontraron que aquellos estudiantes que no participaron en algún programa de prevención de abuso infantil tenían una probabilidad significativamente mayor de sufrir abusos. Así mismo, Apaydin et al (2019), puntualizaron que los niños que recibieron educación sobre prevención de abuso sexual infantil dada por sus padres, mostraron mejor conocimiento sobre las partes privadas y sobre lo que deben hacer si sospechan abuso sexual. A continuación, se presentan diferentes estudios que han dejado evidencia de los programas de intervención para el abuso infantil.…”
Section: Diagnóstico Recibido En La Adultez En Hombres Perpetradores ...unclassified
“…Selain itu, para ibu menonton dua film pendek, tentang berbagai jenis sentuhan, bagian pribadi tubuh dan pelecehan terkait dengan berbagai sentuhan. (7,10,13) , 4 penelitian menggabungkan metode ceramah dengan diskusi kelompok (9,12,15,16) , penelitian menggunakan metode drama dan interview (wawancara) (8) , 1 penelitian menggunakan metode konseling (11) , dan 1 penelitian lainnya menggunaakan metode pelatihan kursus harian (14) . Pemberian program pendidikan didukung dengan penggunaan media seperti leaflet, PPT, lembar worksheet, video/film edukasi, poster edukasi, animasi, gambar/foto, lagu, modul, dan buklet.…”
Section: Tabel 1 Hasil Sintesis Dataunclassified
“…Dari 10 jurnal penelitian yang dianalisis, hanya 5 jurnal yang membahas pemberian pendidikan seksual kepada anak terfokus pada pencegahan child sexual abuse (8,10,11,14,16) Berdasarkan hasil analisis 10 jurnal, beberapa metode intervensi program pendidikan seksual yang efektif untuk diterapkan di Indonesia, yaitu : 1) metode kursus harian yang bersifat estafet dengan melibatkan anak dan orang tua secara langsung; 2) drama edukasi yang dimainkan langsung oleh anak-anak diiringi dengan lagu yang menyenangkan; dan 3) penggunaan lembar worksheet sebagai alat untuk orang tua menyusun konsep pendidikan seksual untuk anak mereka sesuai kehendak mereka dengan tetap mendapat arahan dari fasilitator.…”
Section: Pencegahan Child Sexual Abuseunclassified